Go west and gowes: catatan seorang copywriter/ Budiman Hakim; penyunting Ikhdah Henny & Nurjannah Intan. - BUDIMAN HAKIM; Ikhdah Henny; Nurjannah Intan (B First, 2012)
xii, 264 hlm.: ilus.; 21cm.(3 eks)